Contributions of the enactive perspective to professional university training in Quebec - Grullon Carvajal, Maria del Carmen; Nassif-Gouin, Carine; Trépanier, Nathalie S.; Thériault, Marie (Aurélie); Loiola, Francisco (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2023)
This essay is part of and offers a reflection on the enactive approach to cognition (Varela & al; Thompson, 2007) applied to adult education in Quebec. The objective is to participate in the scientific reflection on professional training in a university context. The preferred content analysis technique derives from the anasynthesis content analysis method (Legendre, 2005; Messier & Dumais, 2016). First, the context of professionalizing university training in Quebec is presented. Then, human activity according to an enactive approach is defined in order to clarify certain key concepts. Finally, examples of applications of enaction in professionalizing university training allow us to explore how an enactive posture supports the professional training of students.